Analisis Postur Kerja Pada Operator Packaging UKM Sirup Yogas Kudus - Sokhibi, Akh; Alfiana, Mia Ajeng; Lusianti, Dina; Wisnujati, Andika (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2020)
Unwittingly, musculoskeletal disorders are complaints that often occur in workers who work in positions that are not ergonomic and persistently. This happened to Yogas Syrup SMEs packaging operator workers. With work facilities in the form of stool chairs, the operator's work position is less comfortable. The purpose of this study was to analyze the work postures of the packaging operator of Yogas Syrup SMEs so that an ergonomic work posture was improved for the operator. The method used in this study is to use the OWAS (Ovako Working Analysis System) method with the help of ergofellow software. The results of this study found that the operator packaging work posture at the UMKM Yogas Syrup was at level 2 (medium potential). This means that the packaging operators at UMKM Syrup Yogas need to get the improved posture and work facilities soon.